2011
DOI: 10.4269/ajtmh.2011.11-0245
|View full text |Cite
|
Sign up to set email alerts
|

Human Antibody Response to Thioredoxin Peroxidase-1 and Tandem Repeat Proteins as Immunodiagnostic Antigen Candidates for Schistosoma japonicum Infection

Abstract: Abstract. Schistosomiasis continues to be a public health problem in many tropical and subtropical countries. Improving the diagnostic tools for surveillance and monitoring in areas that have reached elimination level will help hasten the possible elimination of this disease. This study therefore aims to develop enzyme-linked immunosorbent assay through the use of recombinant proteins such as thioredoxin peroxidase-1 (SjTPx-1) and four tandem repeat proteins (Sj1TR, Sj2TR, Sj4TR, and Sj7TR). Cutoff values wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…Recently, more rapid, sensitive and portable diagnostic assays to detect human antibodies against S. japonicum, have been developed and tested in areas of low endemicity for schistosomiasis japonica in China (Table 3) (3) a time-resolved fluoroimmunoassay (TRFIA), established for detecting Sj14-3-3, as a circulating antigen in serum ; (4) an electrochemical immunosensor array (ECISA) assay (Deng et al 2013) which uses a recombinant S. japonicum calcium-binding protein (SjE16), with SEA, coimmobilized on a disposable 16-channel screenprinted carbon electrode array. So far, a number of candidate antigens have been tested for diagnosing S. japonicum infection; these include Sj23HD ), rSj26GST-Sj32 (Cai et al 2011), SjEFCAB (Lu et al 2012b, SjTPx-1 (Angeles et al 2012) and Sj1TR (Angeles et al 2012), Sj7TR (Angeles et al 2011), SjCHGCS19 (Guo et al 2012), SjLAP , whose characteristics are shown in Table 4. This technique allows the serum-based diagnosis of subjects infected with S. japonicum without the need for sample pretreatment and it can diagnose individuals co-infected with schistosomiasis and TB.…”
Section: Immunological Methodsmentioning
confidence: 99%
“…Recently, more rapid, sensitive and portable diagnostic assays to detect human antibodies against S. japonicum, have been developed and tested in areas of low endemicity for schistosomiasis japonica in China (Table 3) (3) a time-resolved fluoroimmunoassay (TRFIA), established for detecting Sj14-3-3, as a circulating antigen in serum ; (4) an electrochemical immunosensor array (ECISA) assay (Deng et al 2013) which uses a recombinant S. japonicum calcium-binding protein (SjE16), with SEA, coimmobilized on a disposable 16-channel screenprinted carbon electrode array. So far, a number of candidate antigens have been tested for diagnosing S. japonicum infection; these include Sj23HD ), rSj26GST-Sj32 (Cai et al 2011), SjEFCAB (Lu et al 2012b, SjTPx-1 (Angeles et al 2012) and Sj1TR (Angeles et al 2012), Sj7TR (Angeles et al 2011), SjCHGCS19 (Guo et al 2012), SjLAP , whose characteristics are shown in Table 4. This technique allows the serum-based diagnosis of subjects infected with S. japonicum without the need for sample pretreatment and it can diagnose individuals co-infected with schistosomiasis and TB.…”
Section: Immunological Methodsmentioning
confidence: 99%
“…Molecular techniques become research milestones in the detection and diagnosis of schistosomiasis because of their high sensitivity. [41][42][43][44] But one of their limitations is that disease severity, such as the level of hepatic fibrosis in intestinal schistosomiasis, may not be characterized. In addition, other accompanying complications affecting other organs may be neglected.…”
Section: Molecular Techniquesmentioning
confidence: 99%
“…It has been shown that Prx may have diagnostic value for the detection of Leishmania spp., Echinococcus granulosus , Fasciola gigantica , Taenia spp. [8] and Schistosoma japonicum [9]. 1-Cys peroxiredoxin (1-Cys-Prx) in P. falciparum , the orthologous molecule of human Prx VI, is abundantly expressed in the trophozoite stage of P. falciparum [10] making it a promising candidate as a diagnostic antigen.…”
Section: Introductionmentioning
confidence: 99%